Pig characteristics, bio-physical and management aspects that influence rectal temperature in respect to heat stress - Zaake, Paul; Ouma, George O.; Marshall, Karen; Ndambi, A.; Notenbaert, An Maria Omer; Paul, Birthe K.; Dione, Michel M. (2019)
There is limited attention to impacts of climate change on pigs in Uganda by stakeholders despite the potential vulnerability of pigs to climate change, especially heat stress. Pigs are very sensitive to heat stress as they do not have functioning sweat glands (as other livestock species do) and have small lungs which reduces their ability to disseminate heat by panting. Data was collected from 104 households and 259 pigs in Ojwina and Barr sub- counties- Lira district were assessed. Four gender disaggregated focus group discussions were organized. The study was conducted during day in January and early February 2018 against a background of potential heat stress in December and January in pigs. Rectal temperature was the key heat stress indicator as has been widely used by other researchers. For analysis, only pigs whose data was collected in afternoon were considered in the model. Pigs at lower altitude, lactating, castrated, and on free range had higher rectal temperature. The age and heart girth did not significantly influence the rectal temperature of the pig. Air temperature or relative humidity did not independently influence rectal temperature, however the interaction of both air temperature and relative humidity at the pig farm, significantly influenced rectal temperature.